Comparative evaluation of antiulcerogenic action of cryoconserved placenta extract under different modes of introduction - Чиж, М.О.; Кошурба, І.В. (Abstract book of the Annual Conference of Young Scientists "Cold in Biology and Medicine – 2022" (2022 May 25-th, Kharkіv). 2022. Р. 37., 2022)
The study was conducted on 28 male rats weighing 200–220 grams. After 24 hours of fasting, rats were administered intragastrically with prednisolone (20 mg/kg) dissolved in 80.0% ethyl alcohol (0.6 ml/100 grams of animal body weight). The use of alcohol-prednisolone mixture (APM) is justified by the synergism of ulcerogenic action of components – the corticosteroid prednisolone inhibits the biosynthesis of prostaglandins, which leads to a weakening of the resistance of the gastric mucosa (GM). CEP was administered intramuscularly at a dose of 0.16 ml/kg body weight in the prophylactic regimen (1 time per day for 5 days before APM administration) and in the treatment regimen (1 hour after APM administration). Twenty-four hours after APM administration, rats were removed from the experiment and a macroscopic scoring of the GM status was performed and an ulcer index (UI) was calculated. Results. It was found that the prophylactic mode of administration of CEP showed a pronounced antiulcerogenic effect in the model of alcohol-prednisolone gastric ulcer in rats, which indicated a statistically significant (p<0.05) decrease in UI in rats injected CEP compared with control animals in 7, 4 times. In addition, it should be noted that the gastroprotective effect of CEP exceeded the similar activity of the proton pump inhibitor esomeprazole (reference drug) 4 times, which can be attributed to the peculiarities of the chosen mode of administration. At the same time, the treatment regimen of CEP was significantly inferior to the effectiveness of esomeprazole. Thus, UI on the background of the selected cryoextract was 9.3 times higher than in rats administered esomeprazole. Conclusions. CEP has a pronounced anti-ulcerogenic effect in the prophylactic regimen, but is significantly inferior to the reference drug esomeprazole in the treatment regimen. It is advisable to conduct a study of the antiulcer effect of CEP in the combined (therapeutic and prophylactic) mode of administration.
Chyzh M., Koshurba I. Comparative evaluation of antiulcerogenic action of cryoconserved placenta extract under different modes of introduction. Abstract book of the Annual Conference of Young Scientists "Cold in Biology and Medicine – 2022" (2022 May 25-th, Kharkіv). 2022. Р. 37.
Keywords: antiulcerogenic action; cryoconserved placenta extract